PERAN PEREMPUAN DALAM PENCEGAHAN STUNTING DI KECAMATAN BUNAKEN KOTA MANADO PROVINSI SULAWESI UTARA - Timban, Jean Fanny Junita; Tangkere, Ellen Grace; Lumingkewas, Jelly Ribka Danaly (The Studies of Social Sciences, 2020)
Stunting in under-five children is a reduced growth rate primarily caused by chronic undernutrition that leads to a child having height much less than is normal for age. This condition manifests mostly after two years old. The definition of stunting according to the World Health Organization (WHO) is for the "height for age" value to be less than two standard deviations of the WHO Child Growth Standards median. Indonesia has been plagued recently with stunting. In 2015, the World Bank indicates that stunting has cost 3 to 11 percent of the gross domestic product. Previous research works have documented that mothers play an important role in preventing stunting through antenatal care and child nursing. The objective of this study is to explore the role played by the mothers in Bunaken, Manado, in antenatal care and child nursing that prevent stunting. Samples are drawn using purposive sampling and data are analysis descriptively. The results show that the mothers’ roles include taking antenatal check up to four times during pregnancy, daily use of FE 90 pill, participating in pregnancy counseling and care, delivery by health professionals, attending integrated service post (posyandu), visiting health professionals for postnatal care, completing universal immunization on child over 12 months old, and participating in educational activities for under-five nursing and nutritional fulfillment at least once a month. Of these eight recorded roles, however, there are merely 20% mothers indicate they regularly taking part in pregnancy counseling and care. Furthermore, only one percent (n = 3) respondents that report they attending educational activities for under-five nursing and nutritional fulfillment.